Impacts of cruise industry corporate social responsibility reputation on customersâ loyalty: Mediating role of trust and identification - Ahn, J. (Elsevier Ltd, 2021)
Despite the high relevance of Corporate Social Responsibility (CSR) in service businesses, investigations of its influence on the cruise sector are scarce. Relying on institutional theory, this study proposes a model with cruise customersâ trust and identification as the key factors between CSR reputation and customersâ loyalty. Using data from 292 cruise customers, results support the impact of customersâ perceived CSR reputation of cruise companies on two relational constructs and loyal behavior. Only customersâ identification mediates the relationships between reputation and brand loyalty. Thus, findings suggest that cruise customers likely form high-level loyal behavior when they perceive companiesâ CSR activities and their similarities with such companies. From these significant findings, the authors draw several theoretical and practical implications, including the importance of enhancing the company's focus on its CSR reputations. This study also provides directions to promote identity strengths for enhancing the impact of CSR reputation on company performance. Â© 2020 Elsevier Ltd